Artificial intelligence and big data the birth of a new intelligence - Iafrate, Fernando (Information systems, web and pervasive computing series, 2018)
In this book, the author explores the recent technological advances associated with digitised data flows, which have recently opened up new horizons for AI. The reader will gain insight into some of the areas of application of Big Data in AI, including robotics, home automation, health, security, image recognition and natural language processing.